A regeneration method for a metal-deposited deactivated hydrogenation catalyst

The pore structure of the hydrogenation catalyst inactivated by metal deposition is restored through the treatment of propylene oxide solution and acid solution, which solves the problem of reduced catalyst activity, and achieves efficient regeneration and activity recovery of the catalyst, which is suitable for heavy oil hydrotreatment.

CN116920877BActive Publication Date: 2025-08-05CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210353749.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-06
Publication Date
2025-08-05
Estimated Expiration
2042-04-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively restore the activity of hydrogenation catalysts that are deactivated by metal deposition, especially the problem of pore blockage caused by metal impurities such as vanadium and nickel, which leads to a reduction in catalyst activity and difficulty in recovery.

Method used

The propylene oxide solution is used for hydrothermal treatment, combined with the acid solution treatment, the pore structure of the catalyst is restored by sealing heat treatment, and the distribution state of metals in the catalyst is adjusted, including the role of metals such as Ni and V and alumina support.

Benefits of technology

The pore structure and activity of the catalyst are restored, the specific surface area and pore volume of the catalyst are improved, the metal components are distributed evenly, and the activity of the catalyst is enhanced. It is suitable for heavy oil hydrodemetalization and desulfurization processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116920877B_ABST
    Figure CN116920877B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for regenerating a metal-deposited deactivated hydrogenation catalyst, comprising the following steps: (1) deoiling and oxidizing the metal-deposited deactivated hydrogenation catalyst to obtain a pretreated material A; (2) placing the pretreated material A in a propylene oxide solution for hydrothermal treatment, and subjecting the treated material to liquid-solid separation and drying to obtain a hydrothermal treated material B; and (3) impregnating the hydrothermal treated material B with an acid solution and performing a sealed heat treatment again, and subjecting the treated material to drying and calcining to obtain a regenerated catalyst. The method for regenerating the deactivated catalyst can effectively restore the pore structure of the catalyst, regulate the distribution of metals such as Ni and V in the catalyst, and adjust the interaction between the catalyst and the carrier, so that the regenerated catalyst has a high catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalyst regeneration, and in particular relates to a method for regenerating a hydrogenation catalyst deactivated by metal deposition. Background Art

[0002] With the increasing deterioration and heaviness of crude oil, efficient conversion of heavy oil and improved yields of light oil products have become key trends in refining technology. In 2009, global heavy oil hydrocracking and residue hydrotreating capacity reached 266.983 million tons per year, accounting for 61% of total crude oil processing capacity. In 2010, my country imported 239 million tons of crude oil, mostly high-sulfur, low-quality crude from the Middle East. Efficient and clean conversion of these crude oils is a major challenge facing my country's refining industry. Residue hydrotreating technology is an effective means of achieving efficient conversion of heavy oil. This technology effectively removes impurities such as metals, sulfur, nitrogen, and carbon residue from residue oil, providing high-quality feed for catalytic cracking, increasing the production of light oil products while meeting stricter environmental regulations.

[0003] During the hydrogenation reaction, catalyst activity gradually decreases with extended operation time and eventually deactivates. Catalyst deactivation is caused by a variety of factors, including coke deposition. Coke deposits on the catalyst surface clog pores and cover active sites, thereby reducing reaction activity. The majority of catalyst waste in refineries originates from residue hydrotreating units. This is because deactivated catalysts from these units contain, in addition to coke deposits, significant deposits of metal impurities (such as vanadium, nickel, and iron). These metal deposits can exceed 20% of the weight of the spent catalyst. Analysis of the radial distribution of deactivated hydrogenation catalysts revealed that nickel can largely penetrate the interior of the catalyst particles, forming a uniform distribution within the catalyst pores. Vanadium, in most cases, deposits on the surface and near the surface of the catalyst. Once vanadium accumulates in these layers, it clogs the catalyst pores, reducing catalytic activity. This, in turn, leads to the formation of large amounts of carbon and metal deposits on the catalyst surface, ultimately blocking the catalyst pores and completely covering the outer surface, rendering it inactive. Although the deactivation caused by coke can be eliminated by calcination in an oxygen-containing atmosphere, the catalyst deactivation caused by the deposition of metal Ni and V cannot be removed by calcination in an oxygen-containing atmosphere.

[0004] CN1258754A discloses a method for recovering metals from spent Co-Mo catalysts. The method involves calcining the spent catalyst, pulverizing it, dissolving it in ammonia, filtering it, replacing the cobalt in the complex with zinc, then adding nitric acid to recover MoO3, dissolving the filter residue with sulfuric acid, and separating ammonium alum with ammonium sulfate to remove most of the aluminum.

[0005] CN101435027A discloses a method for recovering high-purity molybdenum from molybdenum-containing waste catalysts. The method involves pre-treating the molybdenum-containing waste catalysts, leaching the molybdenum into a solution, and then purifying and recovering the molybdenum from the solution. The pre-treatment of the molybdenum-containing waste catalysts involves thoroughly mixing the crushed waste catalysts with an alkaline substance and magnesium oxide in appropriate proportions, followed by high-temperature calcination.

[0006] When treating deactivated hydrogenation catalysts, the above method can recover valuable metals in the catalysts, but the alumina support material in the catalysts is not effectively utilized.

[0007] CN113000074A discloses a method for regenerating a hydrogenation catalyst. The method comprises: (1) immersing a deactivated hydrogenation catalyst A in a solvent and ultrasonically treating it to obtain a mixture of catalyst B and black powder, recovering catalyst B, and filtering the mixture of catalyst B and black powder to obtain powder C; (2) grinding catalyst B into a powder and sieving it to obtain catalyst powder D; (3) molding, drying, and calcining catalyst powder D to obtain a regenerated carrier; (4) dissolving powder C in liquid paraffin and stirring it; then impregnating it on the regenerated carrier, rapidly cooling it, and then carbonizing it to obtain catalyst E; (5) hydrothermally treating catalyst E to obtain a regenerated hydrogenation catalyst. When using this method to regenerate a deactivated catalyst, the deactivated catalyst needs to be crushed and molded, and then undergo steps such as impregnation, carbonization, and hydrothermal treatment, resulting in a relatively complex process.

[0008] CN102451774A discloses a method for regenerating a deactivated hydroprocessing catalyst. The method comprises: pre-treating the deactivated hydroprocessing catalyst to remove oil, removing metal impurities deposited in the deactivated catalyst, and charring the deactivated catalyst. The method for removing metal impurities deposited in the deactivated catalyst is as follows: impregnating the deactivated catalyst with an alkaline solution, filtering, and then acid washing. While this method can remove metal impurities such as nickel, vanadium, and iron deposited in the deactivated hydroprocessing catalyst and partially restore the pore structure of the catalyst, it also removes the original active metals molybdenum and nickel in the catalyst, which can easily complicate the metal separation and recovery process. In addition, it is not conducive to the recovery of the deactivated catalyst activity.

[0009] Jia Yanzi et al. (Acta Petrolei Sinica (Petroleum Processing) 2010, 26 (4): 635-641) studied the autocatalytic activity of deposited vanadium in the hydrodemetallization reaction of residual oil. The study found that the V deposited in the catalyst would have a certain promoting effect on the catalyst activity. However, due to the complexity of the reaction process, the chemical state, morphology, and the differences in the carrier of V, the utilization of deposited V needs to be further studied. Summary of the Invention

[0010] In response to the deficiencies in the prior art, the present invention provides a method for regenerating a metal-deposited deactivated hydrogenation catalyst. This method is used to regenerate the deactivated catalyst, effectively restoring the pore structure of the catalyst, regulating the distribution of metals such as Ni and V in the catalyst and their interaction with the carrier. The regenerated catalyst has higher catalytic activity.

[0011] The method for regenerating a metal-deposited deactivated hydrogenation catalyst of the present invention comprises the following steps:

[0012] (1) De-oiling and oxidizing the metal-deposited deactivated hydrogenation catalyst to obtain pretreated material A;

[0013] (2) placing the pretreated material A in a propylene oxide solution for hydrothermal treatment, and then subjecting the treated material to liquid-solid separation and drying to obtain a hydrothermally treated material B;

[0014] (3) The hydrothermally treated material B is immersed in an acid solution and subjected to a sealed heat treatment again. The treated material is dried and calcined to obtain a regenerated catalyst.

[0015] In the method of the present invention, the metal deposition deactivated hydrogenation catalyst described in step (1) generally refers to a catalyst that is partially deactivated or fails to meet the reaction requirements due to the deposition of metal impurities such as metal nickel and vanadium during the hydrogenation process of heavy oil or residual oil. The catalyst can be in the form of a cylindrical bar, a clover leaf, a four-leaf clover, a five-tooth sphere or a sphere. The catalyst generally uses alumina or modified alumina as a carrier, and molybdenum and / or tungsten, nickel and / or cobalt as hydrogenation active components.

[0016] In the method of the present invention, the deoiling treatment in step (1) is to remove the reaction oil raw materials from the surface and pores of the deactivated catalyst. The deoiling treatment can generally be carried out by organic solvent extraction treatment or nitrogen extraction treatment. The organic solvent is preferably a mixed solvent of petroleum ether and ethanol. After the extraction treatment, the material is dried. It can be naturally air-dried at room temperature or dried in a forced air oven at a drying temperature of 80-120°C for 4-10 hours until the organic solvent in the material is completely volatilized. The nitrogen extraction treatment is to place the deactivated catalyst in a fixed bed reactor and purge the catalyst with nitrogen until the reaction raw materials on the catalyst surface and in the pores are removed.

[0017] In the method of the present invention, the oxidation treatment conditions in step (1) are: temperature of 450-650° C., time of 1-10 hours, and carried out in an oxygen-containing atmosphere, such as air, preferably in an oxygen atmosphere.

[0018] In the method of the present invention, the pretreated material A obtained in step (1) has a vanadium content of 1% to 10% by weight, preferably 2% to 6% by weight, calculated as oxides, of molybdenum and / or tungsten, of 5% to 20% by weight, and a nickel and / or cobalt content of 3% to 10% by weight, calculated as oxides. The catalyst may also contain impurities such as calcium and iron, and the impurity oxide content is generally less than 1.5%.

[0019] In the method of the present invention, the obtained pretreated material A is preferably subjected to ultrasonic treatment to remove particle deposits on the surface of the spent catalyst. During the ultrasonic treatment, the ultrasonic frequency is 30-40 KHz, the ultrasonic power is 100-150 W, and the ultrasonic time is 10-30 min.

[0020] In the method of the present invention, the mass percentage concentration of the propylene oxide aqueous solution in step (2) is 2.5%-12%, preferably 4%-8%, and the mass ratio of the propylene oxide aqueous solution to the pretreated material is 3:1-10:1, preferably 4:1-8:1. More preferably, polyethylene glycol 2000-20000 is added to the propylene oxide aqueous solution at a mass ratio of the polyethylene glycol 2000-20000 to the pretreated material of 0.01:1-0.05:1.

[0021] In the method of the present invention, the hydrothermal treatment in step (2) is a sealed hydrothermal treatment, which is carried out in a sealed container, preferably an autoclave, and the sealed hydrothermal treatment is carried out in two steps, namely, firstly heat treatment at 60-100°C for 1-4 hours, and then heat treatment at 110-180°C, preferably 120-160°C for 4-8 hours.

[0022] In the method of the present invention, the liquid-solid separation in step (2) can be carried out by conventional filtration, centrifugation, etc.

[0023] In the method of the present invention, the drying temperature in step (2) is 80-160° C., and the drying time is 1-6 hours.

[0024] In the method of the present invention, the acid solution in step (3) is a mixed solution of one or more acids such as acetic acid, oxalic acid, citric acid, and tartaric acid, preferably oxalic acid, and the concentration of the solution is 5wt%-15wt%, preferably 7.5wt%-12.5wt%. A complexing agent is preferably added to the acid solution, and the complexing agent is an organic phosphate, preferably one or more of ethylenediaminetetramethylenephosphate, diethylenetriaminepentamethylidenephosphate, and triethylenetriaminesodiummethylenephosphate, and the concentration of the organic phosphate in the solution is 0.1wt%-0.5wt%.

[0025] In the method of the present invention, the impregnation in step (3) is generally performed by saturated impregnation, and the amount of solution used is the saturated water absorption capacity of the material.

[0026] In the method of the present invention, the sealing heat treatment in step (3) is preferably carried out in an autoclave, with the heat treatment temperature being 40-60° C. and the treatment time being 4-8 hours.

[0027] In the method of the present invention, the drying temperature in step (3) is 80-160°C, the drying time is 4-10 hours, the roasting temperature is 450-550°C, and the roasting time is 4-8 hours.

[0028] The hydrogenation catalyst regenerated by the method of the present invention has the following properties: the specific surface area is 100-180m 2 / g, the pore volume is 0.3-0.6mL / g, the pore diameter is 10-30nm, and the pore volume accounts for 40%-55% of the total pore volume; the vanadium pentoxide content is 1wt%-10wt%, the molybdenum oxide and / or tungsten oxide content is 5wt%-20wt%, and the nickel oxide and / or cobalt oxide content is 3wt%-10wt%.

[0029] The hydrogenation catalyst regenerated by the method of the present invention is suitable for heavy oil hydrodemetallization and hydrodesulfurization processes.

[0030] Compared with the prior art, the present invention has the following advantages:

[0031] (1) The present invention first uses propylene oxide solution to intensively treat the metal deposition deactivated hydrogenation catalyst.

[0032] Sealed heat treatment is carried out in two steps, namely low-temperature heat treatment and high-temperature heat treatment. During low-temperature heat treatment, propylene oxide slowly hydrolyzes to make the solution weakly alkaline. The solution reacts with metal oxides such as molybdenum oxide and / or tungsten oxide and vanadium pentoxide in the catalyst, weakening the reaction between the above metal oxides and the alumina carrier. During high-temperature heat treatment, the alkalinity of the solution is enhanced, further strengthening the effect on metal oxides such as molybdenum oxide and / or tungsten oxide and vanadium pentoxide, causing the metal oxides such as molybdenum oxide and / or tungsten oxide and vanadium pentoxide in the catalyst to be redispersed radially along the catalyst. At the same time, due to the sealed hydrothermal effect of the alkaline solution on the alumina carrier, the specific surface area, pore volume and macropore content of the catalyst are increased, and in particular, the pores on the catalyst surface are made more open.

[0033] (2) When the deactivated catalyst after propylene oxide hydrothermal activation treatment is subjected to acid solution hydrothermal treatment again, the acid solution can effectively improve the interaction between metals such as molybdenum and / or tungsten, nickel and / or cobalt, and vanadium and the alumina carrier. In particular, the addition of the complexing agent makes the interaction between the metal components in the catalyst and the carrier suitable, thereby improving the activity of the regenerated catalyst. In addition, during the sealed heat treatment with the acid solution, the sediments on the catalyst surface and in the pores can be further dissolved, thereby improving the permeability of the pores of the regenerated catalyst. In addition, the acid solution hydrothermal treatment conditions are mild and will not affect the pore structure of the catalyst. The treated catalyst has higher strength.

[0034] (3) The regeneration process regenerates deactivated catalysts with metal deposition, especially a certain amount of vanadium deposition. Since the vanadium content in the deactivated catalyst is appropriate and the interaction between vanadium and the carrier is improved through regeneration, the deposited vanadium is reused as a hydrogenation active component, further improving the activity of the regenerated catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of metal distribution measurement.

[0036] Figure 2 This is a scanning electron microscope image of the surface of the deactivated catalyst after extraction and calcination.

[0037] Figure 3 This is a scanning electron microscope image of the surface of the catalyst ZC-1 after regeneration in Example 1. DETAILED DESCRIPTION

[0038] The technical solutions and effects of the present invention are further described below with reference to the following embodiments, but are not limited to the following embodiments.

[0039] BET method: N2 physical adsorption-desorption was used to characterize the pore structure of the carriers in the examples and comparative examples. The specific procedure was as follows: The sample pore structure was characterized using an ASAP-2420 N2 physical adsorption-desorption instrument. A small amount of sample was vacuum-treated at 300°C for 3-4 hours. Finally, the product was subjected to nitrogen adsorption-desorption testing at low temperatures (-200°C) in liquid nitrogen. The specific surface area was calculated using the BET equation, and the pore volume and pore diameter distribution ratio were calculated using the BJH model.

[0040] XRF characterization: A Rigaku ZSX100e X-ray fluorescence spectrometer was used to analyze the sample composition. The target material was Rh. The optical path atmosphere was vacuum.

[0041] SEM characterization: The microstructure of the samples was characterized using a JEOL JSM-7500F scanning electron microscope with an accelerating voltage of 20 kV.

[0042] EDX characterization: The radial distribution of metals such as molybdenum, nickel, and vanadium in the catalyst was determined using an energy dispersive spectrometer produced by EDAX, a US company. The measurement points were the center of the catalyst cross section and 1 / 4r, 1 / 2r, 3 / 4r, and r from the center. Five samples were selected as parallel samples for each test sample, and three measurement points were measured at the same position for each sample. The average value after measurement was taken as the metal content at that point. See the schematic diagram for details. Figure 1 .

[0043] The sulfur content in oil products was determined using the SH / T 0689-2000 standard method.

[0044] The content of Ni and V in oil products was determined using the GB / T 34099-2017 standard method.

[0045] V+Ni removal rate % = (metal V+Ni content of crude oil - metal V+Ni content of product) / metal V+Ni content of crude oil × 100%.

[0046] Desulfurization rate % = (sulfur content of feedstock oil - sulfur content of product) / sulfur content of feedstock oil × 100%.

[0047] Calculation of relative demetallization rate and relative desulfurization rate: Measure the demetallization rate and desulfurization rate of a certain catalyst, define its relative demetallization rate and relative desulfurization rate as 100%, and the relative deimpurity removal rate of other catalysts / defined catalyst impurity removal rate × 100%.

[0048] The deactivated catalyst used in the examples was a deactivated catalyst from an industrial plant. The catalyst was subjected to extraction to remove oil from the surface, dried, and calcined in an oxygen atmosphere at 600°C for 6 hours. The main components of the treated catalyst were, by weight, MoO3: 10.6%, NiO: 5.3%, V2O5: 6.9%, Al2O3: 75.1%, and P2O5: 0.9%. A scanning electron microscope image of the catalyst surface is shown in FIG. Figure 1 .

[0049] Example 1

[0050] (1) 100 g of the treated catalyst was weighed and ultrasonically treated for 20 minutes in an ultrasonic device with a frequency of 30 kHz and a power of 100 kW. 680 g of a 5.3% by mass propylene oxide solution was added to the catalyst after ultrasonication. 2 g of polyethylene glycol-10000 was then added to the mixture, and the mixture was magnetically stirred for 30 minutes. The mixture was then transferred to an autoclave, sealed, and heated at 65°C for 2 hours. The temperature was then raised to 145°C and heated for 5.5 hours. After cooling, the solid material was filtered, washed, and dried at 110°C for 6 hours to obtain a hydrothermally treated material H.

[0051] (2) The hydrothermally treated material H in step (1) was placed in a spray immersion drum and sprayed with a solution having an oxalic acid concentration of 9.0% and an ethylenediaminetetramethylenephosphate concentration of 0.2% to saturate the material with adsorption. The material was then placed in an autoclave and sealed at 45°C for 5 hours. After treatment, the material was dried at 100°C for 6 hours and calcined at 500°C for 6 hours to obtain a regenerated catalyst ZC1. The catalyst properties are shown in Table 1.

[0052] Example 2

[0053] The same method as in Example 1 was used, except that in step (1), the amount of propylene oxide solution used was 540 g, the mass concentration of propylene oxide in the solution was 6.5%, the treatment temperature for the low-temperature heat treatment was 80° C., the treatment time was 2.5 hours, and the treatment temperature for the high-temperature heat treatment was 135° C., the treatment time was 6.5 hours. In step (2), the mass concentration of oxalic acid in the solution was 10.5%, the organic phosphate was sodium diethylenetriamine penta (methylene phosphate) with a mass concentration of 0.3%, the heat treatment temperature was 50° C., and the treatment time was 6 hours. Regenerated catalyst ZC2 was obtained. The catalyst properties are shown in Table 1.

[0054] Example 3

[0055] The same method as in Example 1 was used, except that in step (1), the amount of propylene oxide solution used was 420 g, the mass concentration of propylene oxide in the solution was 7.4%, the low-temperature heat treatment temperature was 70°C, the treatment time was 3.0 hours, and the high-temperature heat treatment temperature was 155°C, the treatment time was 4.5 hours. In step (2), the mass concentration of oxalic acid in the solution was 7.5%, the heat treatment temperature was 55°C, and the treatment time was 4 hours. Regenerated catalyst ZC3 was obtained. The catalyst properties are shown in Table 1.

[0056] Example 4

[0057] The same method as in Example 1 was used, except that in step (1), the amount of propylene oxide solution used was 760 g, the mass concentration of propylene oxide in the solution was 4.4%, the low-temperature heat treatment temperature was 90°C, the treatment time was 3.0 hours, and the high-temperature heat treatment temperature was 155°C, the treatment time was 1.5 hours. In step (2), the mass concentration of oxalic acid in the solution was 11.5%, the heat treatment temperature was 40°C, and the treatment time was 7 hours. Regenerated catalyst ZC4 was obtained. The catalyst properties are shown in Table 1.

[0058] Example 5

[0059] The same method as Example 1 was used, except that sodium ethylenediaminetetramethylenephosphate was not added in step (2). Regenerated catalyst ZC5 was obtained. The catalyst properties are shown in Table 1.

[0060] Comparative Example 1

[0061] The same method as Example 1 was used, except that the mass percentage concentration of propylene oxide in step (1) was 1.0%. A comparative regenerated catalyst ZC6 was prepared. The catalyst properties are shown in Table 1.

[0062] Comparative Example 2

[0063] The same method as in Example 1 was used, except that the propylene oxide was replaced with the same amount of ethylene oxide to prepare a comparative regenerated catalyst ZC7. The catalyst properties are shown in Table 1.

[0064] Comparative Example 3

[0065] The same method as in Example 1 was used, except that the propylene oxide was replaced with the same amount of distilled water to prepare a comparative regenerated catalyst ZC8. The catalyst properties are shown in Table 1.

[0066] Comparative Example 4

[0067] The same as Example 1, except that in step (1), the mixed material is then transferred into an autoclave and sealed for heat treatment under the conditions of heating at 65°C for 7.5 hours to obtain a comparative regenerated catalyst ZC9. The catalyst properties are shown in Table 1.

[0068] Comparative Example 5

[0069] The same as Example 1, except that in step (1), the mixed material is then transferred into an autoclave and sealed for heat treatment under the conditions of heating at 145°C for 7.5 hours to obtain a comparative regenerated catalyst ZC10. The catalyst properties are shown in Table 1.

[0070] Table 1 Catalyst properties after regeneration

[0071]

[0072] Table 1 Properties of Catalyst after Regeneration

[0073]

[0074] As can be seen from Table 1, the pore volume, specific surface area and 10-30 nanometer pore content of the catalyst regenerated by the method of the present invention are significantly improved, and the metal oxides, especially vanadium, are more evenly distributed in the radial direction of the catalyst.

[0075] Catalytic performance evaluation:

[0076] The catalytic performance of the deactivated catalyst after extraction and calcination (ZC-0), the regenerated catalyst of Example 1 (ZC-1), the regenerated catalyst of Example 3 (ZC-3), the regenerated catalysts of Comparative Examples 1-3 (ZC-5, ZC-6, ZC-7), and the fresh catalyst before operation (Cat-0) were evaluated as follows:

[0077] The catalytic performance of the catalyst was evaluated on a small-scale evaluation device using a residual oil as raw material. The metal (Ni+V) content and sulfur content in the raw oil were 67 μg / g and 2.1 wt%, respectively. The reaction conditions were as follows: reaction temperature of 385°C, hydrogen partial pressure of 13.5 MPa, liquid hourly volume space velocity of 0.6 h -1 The volume ratio of hydrogen to oil was 900. After 500 hours of reaction, the content of each impurity in the generated oil was determined and the impurity removal rate was calculated. The evaluation results are shown in Table 2.

[0078] Table 2 Comparison of catalyst activity

[0079]

[0080] It can be seen from the data in Table 2 that, compared with the deactivated catalyst, the activity of the catalyst regenerated by the method of the present invention is significantly improved. Compared with the fresh catalyst, the activity of the catalyst regenerated by the method of the present invention is better and can be reused.

Claims

1. A method for regenerating a metal-deposited deactivated hydrogenation catalyst, characterized in that The invention comprises the following contents: (1) deoiling and oxidizing the metal-deposited deactivated hydrogenation catalyst to obtain a pretreated material A; (2) placing the pretreated material A in a propylene oxide solution for hydrothermal treatment, and separating the treated material into a liquid-solid state and drying it to obtain a hydrothermal treated material B; (3) impregnating the hydrothermal treated material B with an acid solution and performing a sealed heat treatment again, and drying and calcining the treated material to obtain a regenerated hydrogenation catalyst; the metal-deposited deactivated hydrogenation catalyst in step (1) refers to the metal-deposited deactivated hydrogenation catalyst which is deposited during the hydrotreatment of heavy and residual oils due to the deposition of metal impurities containing nickel and vanadium. The catalyst is partially deactivated or fails to meet the reaction requirements; the oxidation treatment conditions of step (1) are: temperature of 450-650°C, time of 1-10 hours, and carried out in an oxygen-containing atmosphere; the mass percentage concentration of the propylene oxide solution in step (2) is 2.5%-12%; the hydrothermal treatment of step (2) is a sealed hydrothermal treatment, which is carried out in a sealed container. The sealed hydrothermal treatment process is carried out in two steps, firstly, heat treatment at 60-100°C for 1-4 hours, and then heat treatment at 110-180°C for 4-8 hours.

2. The regeneration method according to claim 1, wherein: The deoiling treatment in step (1) is carried out by organic solvent extraction or nitrogen extraction.

3. The regeneration method according to claim 1, wherein: The oxidation treatment in step (1) is carried out under an oxygen atmosphere.

4. The regeneration method according to claim 1, wherein: The pretreated material A obtained in step (1) has a vanadium content of 1%-10% by weight as oxide, a molybdenum and / or tungsten content of 5%-20% by weight as oxide, and a nickel and / or cobalt content of 3%-10% by weight as oxide.

5. The regeneration method according to claim 1, wherein: Before performing step (2), the pretreated material A is subjected to ultrasonic treatment to remove particle deposits on the surface of the spent catalyst. During the ultrasonic treatment, the ultrasonic frequency is 30-40 KHz, the ultrasonic power is 100-150 W, and the ultrasonic time is 10-30 min.

6. The regeneration method according to claim 1, wherein: The mass ratio of the propylene oxide solution used in step (2) to the pretreated material is 3:1-10:

1.

7. The regeneration method according to claim 1, wherein: Polyethylene glycol 2000-20000 is added to the propylene oxide solution, and the mass ratio of the added amount of polyethylene glycol 2000-20000 to the pretreated material is 0.01:1-0.05:

1.

8. The regeneration method according to claim 1, wherein: The acid solution in step (3) is one or more of acetic acid, oxalic acid, citric acid or tartaric acid, and the solution concentration is 5wt%-15wt%.

9. The regeneration method according to claim 1, characterized in that: In step (3), a complexing agent is added to the acid solution, wherein the complexing agent is an organic phosphate.

10. The regeneration method according to claim 9, characterized in that: The organic phosphate is one or more of ethylenediaminetetramethylene phosphate, diethylenetriaminepentamethylene phosphate and aminetrimethylene phosphate. The concentration of the organic phosphate in the acid solution is 0.1wt%-0.5wt%.

11. The regeneration method according to claim 1, characterized in that: The sealing heat treatment in step (3) is carried out in an autoclave at a heat treatment temperature of 40-60° C. for 4-8 hours.

12. The regeneration method according to claim 1, characterized in that: The drying temperature in step (3) is 80-160°C, the drying time is 4-10 hours, the roasting temperature is 450-550°C, and the roasting time is 4-8 hours.

13. The regeneration method according to claim 1, wherein: The regenerated hydrogenation catalyst has the following properties: specific surface area of 100-180m 2 / g, the pore volume is 0.3-0.6mL / g, the pore diameter is 10-30nm, and the pore volume accounts for 40%-55% of the total pore volume; the vanadium pentoxide content is 1wt%-10wt%, the molybdenum oxide and / or tungsten oxide content is 5wt%-20wt%, and the nickel oxide and / or cobalt oxide content is 3wt%-10wt%.

14. Use of a regenerated hydrogenation catalyst obtained by the regeneration method according to any one of claims 1 to 13 in heavy oil hydrodemetallization and hydrodesulfurization processes.

Citation Information

Patent Citations

  • Method for recycling high purity molybdenum from molybdenum-containing spent catalyst

    CN101435027A

  • Method for regenerating inactivated hydrotreating catalyst

    CN102451774A

  • Regeneration method of hydrogenation catalyst

    CN113000074A

  • Recovery process of waste cobalt-molybdenum catalyst

    CN1258754A

  • Regeneration method of inactivated residual oil hydrotreating catalyst

    CN112705211A